Impaired calcineurin signaling in myeloid cells results in downregulation of pentraxin-3 and increased susceptibility to aspergillosis - Zelante, T; Wong, A Y W; Mencarelli, A; Foo, S; Zolezzi, F; Lee, B; Poidinger, M; Ricciardi-Castagnoli, P; Fric, J (Mucosal immunology, 2017)
Treatment of post-transplant patients with immunosuppressive drugs targeting the calcineurin-nuclear factor of activated T cells (NFAT) pathway, including cyclosporine A or tacrolimus, is commonly associated with a higher incidence of opportunistic infections, such as Aspergillus fumigatus, which can lead to severe life-threatening conditions. A component of the A. fumigatus cell wall, β-glucan, is recognized by dendritic cells (DCs) via the Dectin-1 receptor, triggering downstream signaling that leads to calcineurin-NFAT binding, NFAT translocation, and transcription of NFAT-regulated genes. Here, we address the question of whether calcineurin signaling in CD11c-expressing cells, such as DCs, has a specific role in the innate control of A. fumigatus. Impairment of calcineurin in CD11c-expressing cells (CD11ccrecnb1loxP) significantly increased susceptibility to systemic A. fumigatus infection and to intranasal infection in irradiated mice undergoing bone marrow transplant. Global expression profiling of bone marrow-derived DCs identified calcineurin-regulated processes in the immune response to infection, including expression of pentraxin-3, an important antifungal defense protein. These results suggest that calcineurin inhibition directly impairs important immunoprotective functions of myeloid cells, as shown by the higher susceptibility of CD11ccrecnbloxP mice in models of systemic and invasive pulmonary aspergillosis, including after allogeneic bone marrow transplantation. These findings are relevant to the clinical management of transplant patients with severe Aspergillus infections.
Keywords: rejekce štěpu; kultivované buňky; signální transdukce; C-Reactive Protein; Immunosuppressive Agents; antigeny CD11c; Mice, Inbred BALB C; Aspergillosis; náchylnost k nemoci; C-reaktivní protein; down regulace; myši inbrední C57BL; aspergilóza; Signal Transduction; Mice; Calcineurin Inhibitors; myši knockoutované; Down-Regulation; Aspergillus fumigatus; Dendritic Cells; sérový amyloidový protein; Cells, Cultured; CD11c Antigen; Serum Amyloid P-Component; dendritické buňky; zvířata; inhibitory kalcineurinu; imunosupresiva; Graft Rejection; Humans; myši inbrední BALB C; Disease Susceptibility; kalcineurin; Mice, Knockout; Bone Marrow Transplantation; myši; transplantace kostní dřeně; Calcineurin; Mice, Inbred C57BL; lidé; Animals